DEVELOPMENT AND APPLICATION OF STEER-BY-WIRE (SBW) WITH LINEAR SENSORS TO A SMALL ELECTRIC VEHICLE - Ismail, Hasan; Kusuma, Fuad Indra; Harly, Moch; Nasir, Mohd Zakaria B Mohammad (Universitas Negeri Yogyakarta, 2024)
A steer-by-wire (SBW) system with linear sensors has been developed and implemented on a small electric vehicle (EV). This system comprises a steering wheel, an angle and torque sensor, a wheel angle feedback sensor, an electric motor actuator, linkages, and a controller. It is specifically designed to electrically control the wheel angles without utilizing a conventional steering gearbox. The electric actuator motor is mounted on the steering mechanism and directly connected to the left and right wheel knuckles via linkages. Two linear sensors are employed: one located on the steering wheel to generate steering wheel angle signal , and the other installed on the wheel knuckle mechanism to produce front wheel angle feedback signal . When the driver rotates the steering wheel, the controller calculates the pitch error based on inputs from the two linear sensors and subsequently adjusts the wheel angles by powering the electric motor actuator. Experimental testing revealed a response time of 0.3 seconds, with the pitch error maintained within an angle of less than 3° during straight-motion tests. During cornering motion tests, the measured backlash was approximately 0.06 rad, demonstrating the system's responsive performance. This SBW technology with linear sensors is anticipated to reduce system complexity while enhancing precision, accuracy, and response speed of wheel angle adjustments to steering inputs, effectively meeting driving requirements.